Metagenomic and proteomic approaches in elucidating aflatoxin B1 detoxification mechanisms of probiotic Lactobacillus casei Shirota towards intestine - Liew, Winnie Pui Pui; Sabran, Mohd Redzwan; Leslie, Thian Lung Than; Abd Ghani, Fauzah (Elsevier, 2022)
The modulation of gut microbiota and proteome due to aflatoxin B1 (AFB1) by probiotics remains unclear. This study investigated the alterations of gut microbiota and proteome in AFB1-exposed rats treated with probiotic Lactobacillus casei Shirota (Lcs). Forty male Sprague Dawley rats were randomly divided into five groups (n = 8) comprised control, AFB1, AFB1+activated charcoal, AFB1+Lcs, and Lcs groups. The rats were subjected to different treatments via oral gavage for four weeks. Urine and serum were collected for the measurement of AFB1 biomarkers and organs were harvested for histological analysis. Metagenomic sequencing was performed on fecal samples to profile gut microbiota. Besides, AFB1 most affected organ i.e. jejunum was subjected to proteomic analysis. The results indicated that Lcs intervention significantly reduced AFB1 biomarkers. H&E-stained intestine showed Lcs alleviated AFB1-induced inflammation and abnormal cell growth, particularly at the jejunum. Although AFB1 increased potentially pathogenic bacteria and reduced beneficial bacteria abundance in feces, the microbiota composition was normalized with Lcs treatment. The gut proteome analysis of the jejunum sample showed several pathways of AFB1 toxicity, wherein Lcs treatment demonstrated its protective effect. It is concluded that metagenomic and proteomic approaches are useful tools to understand AFB1-Lcs interaction and detoxification mechanism in the gut.